A comparative study of the static balance ability of Chinese disabled and normal swimming athletes - Wu, S.; Tang, G.; Wang, Z. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study was to evaluate the ability of swimmers with a disability to control their body`s center of gravity using tests of static balance ability. Findings from the study will provide insight into optimal training strategies. Methods Twelve. swimmers with a disability and 8 normal swimming athletes were subjects for the study. The `GOOD BALANCE` training testing system was used. Data recorded included: Dx1: the ratio between the moving distance of the centre of pressure (COP) in the X direction and the width of the left foot when standing on this foot with eyes open. Dy1: the ratio between the moving distance of centre of pressure (COP) in the Y direction and the length of the left foot when standing on this foot with eyes open.. Dx2: the ratio between the moving distance of the centre of pressure (COP) in the X direction and the width of the right foot when standing on this foot with eyes open. . Dy2: the ratio between the moving distance of the centre of pressure (COP) in the Y direction and the length of the right foot when standing with eyes open. Dx3: the ratio between the moving distance of the centre of pressure (COP) in the X direction and the width of both feet when standing on both feet in the long axis with open eyes. Dy3: the ratio between the moving distance of the centre of pressure(COP) in the Y direction and the length of both feet when standing on both with the eyes open. Dx4: the ratio between the moving distance of the centre of pressure (COP) in the X direction and the width of both feet when standing on both feet in long axis with closed eyes. Dy4: the ratio between the moving distance of the centre of pressure (COP) in the Y direction and the length of both feet when standing on both feet in the long axis with eyes closed. To gain the relevant knowledge, interviews of swimming experts, biomechanics experts and psychology experts were alsoundertaken. The data collected was applied to SPSS software for statistical analysis. Results Swimmers with a disability recorded the following outcomes: Dx1:7.03±1.73, Dy1:2.79±1.00, Dx2:6.13±2.63, Dy2:2.25±0.47, Dx3:5.00±1.73, Dy3:1.06±0.42, Dx4:10.89±2.33, Dy4:2.21±0.58; In contrast normal swimming athletes recorded the following: Dx1:6.52±1.66, Dy1:2.26±0.49, Dx2:6.39±1.36, Dy2:1.96±0.32, Dx3:4.59±1.02, Dy3:0.81±0.24, Dx4:8.53±2.63, Dy4:1.57±0.62. There were significant differences between the disabled athletes and the normal swimming athletes in Dy4 (p <0.05). Discussion / Conclusions No significant differences in balance ability between normal swimming athletes and swimming athletes with a disability were found when standing on one foot. This finding suggests that the ability to control the body`s centre of gravity of the outstanding disabled swimming athletes was superior to that of the non-disabled group. When standing on both feet in long axis, there were no significant differences between the groups when tested with the eyes open. However, there were significant differences in the eyes closed test in the y-axis direction. Although there are significant differences with respect to the degree of disability in swimmers, the tests of balance used in this study may be useful in determining differences and changes in the physical control centres with increases in the level of physical movement. The corresponding test methods may also be designed according to the swimmers` dynamic characteristics. Due to different degrees of disability, there are great differences in focus for disabled swimmers and strengthening control of the training centre (Y-axis) is the key to improving performance.